2021
DOI: 10.9745/ghsp-d-20-00380
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Knowledge of Community Health Workers at the Last Mile in Liberia: Feasibility and Results of Clinical Vignette Assessments

Abstract: We integrated clinical vignettes into routine programmatic supervision to assess community health worker knowledge of integrated community case management in rural Liberia. Results included higher rates of correct diagnosis and lifesaving treatment for uncomplicated disease than for more severe cases, with accurate recognition of danger signs posing a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The trend was the same for the two additional DRC-specific signs triggering RAS use, although the association was not significant in children suffering from “weakness or asthenia”. Findings from Liberia have shown that the proportions of correct diagnosis and treatment by community-based healthcare providers varied substantially for uncomplicated disease, but consistency was better for more severe cases, even though the accurate recognition of danger signs was sub-optimal [ 38 ]. Findings from this study suggest that danger signs increase substantially the probability of receiving RAS, but not subsequent referral and treatment at a RHF.…”
Section: Discussionmentioning
confidence: 99%
“…The trend was the same for the two additional DRC-specific signs triggering RAS use, although the association was not significant in children suffering from “weakness or asthenia”. Findings from Liberia have shown that the proportions of correct diagnosis and treatment by community-based healthcare providers varied substantially for uncomplicated disease, but consistency was better for more severe cases, even though the accurate recognition of danger signs was sub-optimal [ 38 ]. Findings from this study suggest that danger signs increase substantially the probability of receiving RAS, but not subsequent referral and treatment at a RHF.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of precursor programs to Liberia's National CHA Program found substantial improvements in childhood illness care seeking from a qualified provider, including consistent improvements in care for childhood fever, diarrhea, and acute respiratory illness by qualified providers [11,12]. Further, Liberian community health assistants have been found to have acceptable levels of knowledge about childhood disease treatment [25]. Finally, a recent analysis of Liberian District Health Information System data found that, in areas served by community health assistants after the launch of the NCHAP program, a little over half of malaria diagnoses had shifted from facilities to community health assistants, 95% of diagnoses were confirmed with RDT or microscopy, and diagnosis appeared to be sustained during the first nine months of the covid-19 pandemic [26].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the trend was the same for the two additional signs triggering RAS use in DRC, although the association was not significant in children suffering from asthenia (weakness). Findings from Liberia have shown that the proportions of correct diagnosis and lifesaving treatment varied, especially for uncomplicated disease, but that the variability was lower for more severe cases, even though the accurate recognition of danger signs was sub-optimal (34).…”
Section: Discussionmentioning
confidence: 99%